State structure, policy formation, and economic development in Southeast Asia structuring development the political economy of Thailand and the Philippines - Raquiza, Antoinette (Routledge studies in the growth economies of Asia (2005), 2012)
"This book considers late developing market economies, exploring the differences in performance in these economies, which are particularly vulnerable to political turmoil, crony capitalism and external shocks."--Publisher's description.